DEVELOPING THE LOCAL POLITICAL SPACE FOR INCLUSIVE NAGARI PASIA LAWEH INSTITUTIONS IN WEST SUMATERA - Valentina, Tengku Rika; Putera, Roni Ekha (JWP (Jurnal Wacana Politik), 2024)
This study focuses on the local political sphere by examining the policies and the spread of Nagari’s institutional structure in West Sumatra by following Law No. 6 of 2014 about Villages. We examine and reassess the new variations of the local political sphere, focusing on local elites (Penghulu-Alim Ulama) and local communities’ growth within Nagari institutions in West Sumatra. Data was gathered via a focus group discussion (FGD) including stakeholders, regency administration, the Nagari government, and the communities. The findings are Nagari Pasia Laweh envisions an advanced Nagari based on local wisdom and open dialogue. It possesses benefits that effectively empower all community members in the process of the policy cycle. Law No. 6 of 2014 provides the Nagari government with opportunities to participate in policy formation and decision-making processes. The Nagari government greatly benefits, including financial and material aid from the central government and contributing significantly to its overall advancement. Participation of local elites, such as ninik mamak, penghulu, and traditional stakeholders at every stage of the policy process enhances the effectiveness of accountability mechanisms, facilitating the collective implementation and evaluation of policies.